Respiratory severity score and extubation readiness in very low birth weight infants - Maroun J. Mhanna; Narayan P. Iyer; Scott Piraino; Mohit Jain (Elsevier, 2017)
Background: The respiratory severity score (RSS) is a byproduct of mean airway pressure (MAP) and fraction of inspired oxygen (FiO2). We sought to determine whether RSS could be used as a screening tool to predict extubation readiness in very low birth weight (VLBW) infants. Methods: In a retrospective cohort study, medical records of all VLBW infants admitted to our unit (6/1/09â2/28/12) were reviewed for infants' demographics, prenatal characteristics, and medication use. Also, records were reviewed for unplanned vs. planned extubation, blood gas, ventilator parameters and signs of severe respiratory failure [RF, defined as partial pressure of carbon dioxide (pCO2)Â >Â 65, pHÂ <Â 7.20, FiO2Â >Â 50%, and MAPÂ >Â 10Â cm] on the day of extubation. Results: During the study period 31% (45/147) failed extubation. Overall, infants who failed extubation had a lower birth weight (BW) and gestational age (GA), and on the day of extubation had a higher RSS and percentage of having one or more signs of severe RF. In a logistic regression model, adjusting for BW, GA, RSS and RF, RSS remained the only risk factor associated with extubation failure [adjusted OR 1.63 (95% CI: 1.10â2.40); pÂ =Â 0.01]. RSS had a sensitivity of 0.86 (95% CI: 0.72â0.94) at a cutoff of 1.26 and a specificity of 0.88 (95% CI: 0.80â0.94) at a cutoff of 2.5. There was no difference in extubation failure between unplanned vs. planned extubation [41% (9/22) vs. 29% (36/125); pÂ =Â 0.25]. Conclusion: An elevated RSS is associated with extubation failure. Successful unplanned extubation is common in VLBW infants. Key Words: very low birth weight, extubation, mechanical ventilation, respiratory severity score